Proceedings of International Conference on ICT for Sustainable Development ICT4SD 2015 Volume 1 - Satapathy, Suresh Chandra; Joshi, Amit; Modi, Nilesh; Pathak, Nisarg (Advances in Intelligent Systems and Computing,, 2016)
The two volumes of this book collect high-quality peer-reviewed research papers presented in the International Conference on ICT for Sustainable Development (ICT4SD 2015) held at Ahmedabad, India during 3 - 4 July 2015. The book discusses all areas of Information and Communication Technologies and its applications in field for engineering and management. The main focus of the volumes are on applications of ICT for Infrastructure, e-Governance, and contemporary technologies advancements on Data Mining, Security, Computer Graphics, etc. The objective of this International Conference is to provide an opportunity for the researchers, academicians, industry persons and students to interact and exchange ideas, experience and expertise in the current trend and strategies for Information and Communication Technologies.